Sistem Informasi Penilaian Keselamatan Jalan Tol Dengan Menggunakan Star Rating Berbasis Webgis (Studi Kasus : Jalan Tol Cikopo-Palimanan) - Dwiyantara, Arga; Budiharjo, Anton; Suradji, Djarot (Jurnal Keselamatan Transportasi Jalan (Indonesian Journal of Road Safety), 2019)
The highway is one solution to improve the smoothness of the traffic. Service with a verysmall side constraints make this road used as an option for road users to get to thedestination quickly. Ho wever, with the increase in the highway users, then the level ofhighway services should be tailored to the needs of the service. Based on those deemed toogeneral to be used in assessing the safety performance of highway infrastructure. Based onthese problems required great value for each of the indicators that affect highway safety anddesign of Information Systems Highway Safety Assessment. With the aim of the study,appropriate research methods is the method of Research and Development, known by theterm Research and Development (R & D). After the analysis, it can be seen that the impactof the highway Cipali each section has a value range between 60-100 and star rating on thehighway Cipali that there are 3 and 4 in each section.